PHYSICAL COMPOSITION OF BROILER CARCASSES FED COMMERCIAL DIETS SUBSTITUTED WITH FERMENTED BAKERY WASTE - A., Firman; Oka, A. A.; Suarta, I G. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
This study aims to determine the physical composition of broiler carcasses fed commercial rations substituted with fermented bread waste. This research was conducted at the Farm of Faculty of Animal Husbandry, Udayana University, Jalan Raya Sesetan, Denpasar. Submitted Date: May 30, 2023 Accepted Date: September 3, 2023 Editor-Reviewer Article: Eny Puspani & A.A. Pt. Putra Wibawa Firman, A., Peternakan Tropika Vol. 12 No. 2 Th. 2024: 1 – 16 Page 2 Laboratory analysis was carried out in the laboratory of nutrition and animal feed, Faculty of Animal Husbandry, Udayana University, Jalan P.B. Soedirman, Denpasar. This study lasted for 2 months, starting from December 20, 2022 to January 24, 2023 using a completely randomized design consisting of 5 treatments and 4 replications. Each experimental unit was filled with 4 broilers that had a homogeneous body weight ranging from 51.07 ± 5.53g. The five treatments consisted of P0 (100% commercial ration), P1 (90% commercial ration + 10% Probiotic fermented bread waste flour), P2 (85% commercial ration + 15% Probiotic fermented bread waste flour), P3 (80% commercial ration + 20% Probiotic fermented bread waste flour), and P4 (75% commercial ration + 25% Probiotic fermented bread waste flour). The observed variables were slaughter weight, carcass weight, carcass percentage, meat percentage, fat percentage, and bone percentage. The results showed that the provision of rations with the substitution of bakery waste and "Probio-BaliTani" had a significant effect on slaughter weight, carcass weight and meat percentage (P 0,05). Based on this study, it can be concluded that giving commercial rations with bread waste substitution reduces slaughter weight, carcass weight, meat percentage and has no effect on carcass percentage, fat percentage, and bone percentage, but reduces ration price.